Prevalence and factors associated to the types of esophageal cancer in Hospital Nacional Arzobispo Loayza during 2009 to 2013 - Norabuena Huapaya, Luis Andrés (2015)
Objective: To determine the prevalence and the risk factors associated with the different types of esophageal cancer in Hospital Nacional Arzobispo Loayza during2009-2013. Material and Methods: This study was a retrospective cohort study. The population studied was patients that had already been diagnosed with esophageal cancer and treated in the GE Department of Hospital Nacional Arzobispo Loayza during the period of2009-2013. Inclusion criteria used were patients older than 18 years old with complete histological diagnosis of esophageal cancer. Results: 70% of patients were found to have squamous cell carcinoma and 30% were found to have esophageal adenocarcinoma. Alcohol consumption was present in 66.7% of patients with adenocarcinoma and 37.1% of patients with squamous cell carcinoma. Tobacco use was more in patients with adenocarcinoma with a 60% compared to a 34.3% in patients with squamous cell carcinoma. Esophagitis was found to have an association with squamous cell carcinoma. Clinical manifestations such as dysphagia, weight loss and melena were almost 50% of all clinical manifestations of both types of esophageal cancer. Conclusion: Patients 65 years old or older, alcohol consumption, tobacco use and male gender are factors associated with adenocarcinoma. Esophagitis was found to bea factor associated with squamous cell carcinoma. We found an increase in the prevalence of adenocarcinoma in the population, following world tendencies that indicate that there is a significant increase. We found a smaller prevalence compared to more developed countries.